Linguistic, Cognitive, and Environmental Barriers to English Paragraph Writing: A Mixed-Methods Study of Indonesian EFL Students - Nur, Nur Syamsiah; Agus Muhamad Bintang (JADEs Journal of Academia in English Education, 2025)
Writing English paragraphs remains a significant challenge for many EFL students at UIN Raden Intan Lampung, a public Islamic university characterized by diverse linguistic and academic backgrounds. This study investigated the linguistic, cognitive, and environmental barriers to English paragraph writing through a convergent parallel mixed-methods design. Quantitative data were collected via questionnaires from 60 students, complemented by semi-structured interviews with 10 participants for qualitative insights. Results showed that linguistic difficulties, especially vocabulary limitations (78%) and grammar issues (65%), were the most prevalent obstacles. Cognitive challenges such as idea generation (48%) and paragraph organization (42%) also considerably affected students’ writing performance. Additionally, 25% of students identified environmental factors noisy classrooms and limited writing time as disruptive influences. Interview data revealed that vocabulary problems stemmed from minimal English exposure and ineffective learning strategies, while grammar struggles were linked to heavy reliance on L1 translation, influenced by students’ religious education. These findings align with Swain’s Output Hypothesis, emphasizing the role of active language production in writing development. By addressing gaps in Indonesian EFL research, this study highlights the complex, overlapping barriers faced by students in Islamic university settings and recommends integrated instructional approaches